(untitled) (Journal of Hama University, 2026)
This study aimed to investigate the prevalence of Capillaria spp. infections in chickens in Hama Governorate, Syria, and to analyze the factors influencing infection rates. A total of 1,601 fecal samples were collected from local chickens and intensively reared commercial hybrid chickens between March 4, 2024, and March 4, 2025. Laboratory examination was performed using gross examination, direct smear, and flotation concentration methods. Data were statistically analyzed using the Chi-Square test at a significance level of P<0.05. The results showed that the overall prevalence was 7.87%. The highest infection rate was recorded in the western region (27.35%) and the lowest in the eastern region (0%). Infection rates were significantly higher in free-range local chickens (22.79%) compared to commercial hybrids (1.35%), and in older birds (≥ 1 year) compared to younger ones, peaking at 3 years of age (26.04%). Seasonal variation was observed, with the highest prevalence in autumn (23.04%) and no infections detected in winter. These findings highlight the importance of monitoring Capillaria spp. infections, particularly in free-range local breeds, older age groups, and during the autumn season, and emphasize the need for effective control programs to minimize their impact on poultry health and productivity.